HIPK2 Is Required for Midbody Remnant Removal Through Autophagy-Mediated Degradation - Sardina, Francesca; Monteonofrio, Laura; Ferrara, Manuela; Magi, Fiorenza; Soddu, Silvia; Rinaldo, Cinzia (Frontiers in Cell and Developmental Biology, 2020)
At the end of abscission, the residual midbody forms the so-called midbody remnant (MBR), a platform affecting cell fate with emerging key role in differentiation, development, and tumorigenicity. Depending on cell-type and patho-physiological context, MBRs undergo different outcomes: they can be retained, released, internalized by nearby cells, or removed through autophagy-mediated degradation. Although mechanisms underlying MBR formation, positioning, and processing have been recently identified, their regulation is still largely unknown. Here, we report that the multifunctional kinase HIPK2 regulates MBR processing contributing to MBR removal. In the process of studying the role of HIPK2 in abscission, we observed that, in addition to cytokinesis failure, HIPK2 depletion leads to significant accumulation of MBRs. In particular, we detected comparable accumulation of MBRs after HIPK2 depletion or treatment with the autophagic inhibitor chloroquine. In contrast, single depletion of the two independent HIPK2 abscission targets, extrachromosomal histone H2B and severing enzyme Spastin, only marginally increased MBR retention suggesting that MBR accumulation is not just linked to cytokinesis failure. We found that HIPK2 depletion leads to i) increased levels of CEP55, a key effector of both midbody formation and MBR degradation; ii) decreased levels of the selective autophagy receptors NBR1 and p62/SQSTM1; and iii) impaired autophagic flux. These data suggest that HIPK2 contributes to MBR processing by regulating its autophagy-mediated degradation.